Transformasi Digital pada Sistem Informasi Perbankan dan Keputusan Bertransaksi pada Bank Syariah: Kasus di Indonesia - Christina Ika Ningrum; Agus Eko Sujianto; Mochamad Arif Faizin (Jurnal Penelitian Teori & Terapan Akuntansi (PETA), 2023)
This study aims to examine the role of digital transformation in banking information systems on transaction decisions in Islamic banks. This research was conducted in Indonesia with a quantitative method with a survey. Respondents' perceptions that can be analyzed are 391 respondents and tested using simple linear regression. The findings contribute to empirical evidence that digital transformation in banking information systems has a positive effect on transaction decisions in Islamic banks. These findings have implications for digitization in banking, directly or indirectly, having a positive impact on increasing customers using Islamic banks, which in turn can increase the market share of Islamic banks in Indonesia.